MODELAMIENTO DE HABILIDADES EN MODELOS 3-IRT DE RESPUESTA AL ITEM - Cepeda Cuervo, Edilberto; Peláez Andrade, José Manuel (Revista Colombiana de Estadística, 2004)
This paper considers situations where regression models are proposed to model abilities on three parameter logistic models. After a summary of the classical approach to estimate the item parameters and the abilities, we provide an exposition of the maximum likelihood method to estimate the regression parameters. We analyze how good these estimations are, using a simulated study, and we include an application.